Competitive conditions among the major British banks - Matthews, Kent; Murinde, Victor; Zhao, Tianshu (Journal of Banking & Finance, 2007)
This paper reports an empirical assessment of competitive conditions among the major British banks, during a period of major structural change. Specifically, estimates of the Rosse–Panzar H-statistic are reported for a panel of 12 banks for the period 1980–2004. The sample banks correspond closely to the major British banking groups specified by the British Banking Association. The robustness of the results of the Rosse–Panzar methodology is tested by estimating the ratio of Lerner indices obtained from interest rate setting equations. The results confirm the consensus finding that competition in British banking is most accurately characterised by the theoretical model of monopolistic competition. There is evidence that the intensity of competition in the core market for bank lending remained approximately unchanged throughout the 1980s and 1990s. However, competition appears to have become less intense in the non-core (off-balance sheet) business of British banks.